Where Were European Higher Education Institutions within Erasmus Mundus Action2 Strand 1? - Perez, Mariano Martin (European Scientific Journal, ESJ, 2018)
Teichler (2009) wrote â€œERASMUS was a trigger for a qualitative leap of internationalisation strategies and policies since the 1990s: towards cooperation and mobility on equal terms, and towards systematic and strategic internationalisationâ€. Though, one might say, Higher Education Institutions (HEIs) follow that path with the aim of generating, strengthening and promoting said qualitative leap including within their institutional structures. The European Union struggled for each and every one of the HEIs to be strengthened by means of a program that allowed them to strengthen their internationalization process and give them an equality of conditions, at an EU level, as receptors of help to participate in international activities. In this sense, this study will provide an unconventional understanding of the EUâ€™s HEIsâ€™ participation level, and will try to open a debate to discuss at further depth as to how much they were able to be equal beneficiaries of the Erasmus Mundus Action 2 Strand 1. This research is part of a doctoral investigation project. It was structured as a descriptive study and it utilized secondary information which came from data published by the EACEA on its website as well as from different online documents. According to the studyâ€™s findings, the EMA2S1 was an open tool for all European HEIs, but it benefitted only some of them.